Tafsir Al-Baidawi Pada Era Afirmasi Islam Klasik: Kajian Atas Anwar Al-Tanzil Wa Asrar Al-Ta'wil - Aghnia Faradits (Studia Quranika, 2025)
Al-Baiḍāwī's Anwār Al-Tanzīl Wa Asrār Al-Ta’wīl is one of the most phenomenal tafsir books of its time. This tafsir book is interesting to discuss because it is rich in religious schools adhered to by the exegete. One of the reasons for the richness of religious schools in this tafsir is suspected to be because Al-Baiḍāwī lived in a situation of tension between groups within each discipline of Islamic science. In this study, the author uses the content analysis method to interpret and identify the tafsir book mentioned above. In addition, the explanatory method was chosen to find the message of the interpreter so that it can be understood and taken. It was found that first: the interpretation of Anwār Al-Tanzīl Wa Asrār Al-Ta’wīl is the result of mukhtaṣar from the interpretation of al-Kasysyāf by al-Zamakhsyari which is in the Mu’tazilah genre, and the interpretation of Mafātiḥ al-Ghaib by Fakhruddin al-Rāzī which is in the Ahlussunnah wal Jama’ah genre, but he avoided Zamakhsyari’s views which contain elements of Mu’tazilah understanding. Second: When interpreting the verses of tajsim, Al-Baiḍāwī presented them concisely and showed his tendency towards the Shafi’i school of thought which he adhered to. Third: Al-Baiḍāwī in his work, not only interpreted, but also provided interpretations of the verses of the Qur'an using an approach based on Arabic language rules.